LODGVis - An Interactive Visualization for Linked Open Data Navigation - Coimbra, Danilo B.; Negrão, José O. M.; Durão, Frederico A. (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2019: Proceedings of the 25th Brazilian Symposium on Multimedia and the Web, 2019)
The amount of structured data available on the Web in semantic formats have been growing enormously in recent years. In this scenario, Linked Data effort is essential to retrieve detailed information from the Web, especially if we consider the importance of the Web in our daily lives and activities. However, there is a lack of tools and techniques that allow users to properly navigate on Linked Data formats, such as Resource Description Framework (RDF) documents. This work aims to present LODGVis, a novel interactive visualization technique that enables navigation throughout RDF documents. This technique was developed as an open source Web application and provides a visual exploratory approach that allows users to freely browse semantic data through graphs-base visualization considering several features, including customization, aggregation and multiple level navigation. Our study case considers DBpedia data set, but our technique can be easily extended to any RDF-based data set.